Pengaruh mckenzie extension exercise terhadap tingkat penurunan skala nyeri punggung bawah - Suputri, Putu Pande Eka; Damayanti S., Made Rini; Gandasari, Ni Mas Ayu (Coping: Community of Publishing in Nursing; Vol 6 No 2 (2018): Agustus 2018, 2019)
Low back pain is the high risk of office workers which characterized of pain in the lower spine. The treatment of low back pain can be solved with non-pharmacological therapies named back exercise specifically mckenzie extension exercise training. The purpose of this study was to determine the effect of mckenzie extension exercise to the decreased level of low back pain scale on employees at Sistim Manunggal Satu Atap (Samsat) Office of Karangasem regency. This research method was pre-experimental approach to one group pre-post test design with purposive sampling technique. Data analysis used non-parametric statistical methods Wilcoxon Signed Rank Test. This study was conducted on May 12th to 22th 2015 at Sistim Manunggal Satu Atap (Samsat) Office of Karangasem regency with the sample of 40 people. The results of this study found that the value of p = 0.000 (p <0.05) and interpreted there was a significant impact between mckenzie extension exercise to the decrease level of low back pain scale on employees at Sistim Manunggal Satu Atap (Samsat) Office of Karangasem regency. The result of this study can be a recommendation for employees at Sistim Manunggal Satu Atap (Samsat) Office of Karangasem regency in order to increase the level of health, specially to decrease the pain scale of low back pain.
Keywords: McKenzie Extension Exercise, Low Back Pain